Genetic analysis and quantitative trait locus identification of the reproductive to vegetative growth period ratio in soybean (Glycine max (L.) Merr.) - Wang, Ying; Cheng, Lirui; Leng, Jiantian; Wu, Cunxiang; Shao, Guihua; Hou, Wensheng; Han, Tianfu (Euphytica, 2015)
The total growth duration (TGD), the days from emergence to maturation of the soybean, can be divided into vegetative period (VP) and reproductive period (RP). The ratio of RP to VP (R/V) is an index to investigate evolutionary trends and understand the relationships between different growth periods. To increase our understanding of growth period traits with emphasis on R/V, four generation segregated populations, including P 1 , P 2 , F 1 , F 2 , and F 2:3 were constructed. Joint segregation analysis revealed that R/V was controlled through major genes plus polygenes. QTL mapping result showed that a total of 22 QTLs were associated with growth period traits. One major effect QTL for R/V, qR/V-1, was mapped on the C2 linkage group, and accounted for 46.90 and 33.72 % of the phenotypic variance under spring and summer sowing season conditions, respectively. The parent bands of the major gene were ubiquitous in the soybean germplasms. The chromosome adjacent interval of qR/V-1 was proved to be associated with VP, TGD, RP, and photo-thermal sensitivity of R/V. However, the QTL showed different effects on different growth period traits. In addition, the 2 minor-effect QTLs for R/V could not be detected repeatedly for others growth period traits. These results indicated that the R/V were controlled through differential pathways with other growth period traits, although one major effect QTL was mapped to the same region.